SNP associations in the L-citrulline metabolic pathway and vascular aging in the Japanese population - Dai Nogimura; Kazuki Moriyasu; Sachiko Ishida; Masakazu Kohda; Takayuki Yazawa; Masahiko Morita (PLoS ONE, 2025)
Decreased nitric oxide (NO) production from the vascular endothelium is a major factor for vascular aging. Because vascular aging has few specific subjective symptoms, assessing the susceptibility to vascular aging is beneficial for its early detection and improvement. Therefore, this study evaluated the associations between single nucleotide polymorphisms (SNPs) on L-citrulline (Cit) pathways essential for NO production and the health characteristics involved in vascular aging using a candidate gene approach. Associations with a significance level included those between the KCNMB4 rs17108108 C allele and tendency to gain weight, the ADCY8 rs6470860 G allele and numbness of limbs, the NOS1 rs2271987 T allele and lower back pain, and the PDE9A rs2284972 G allele and body pain with negative mood states. A genome-wide association study was also conducted to analyze SNPs more extensively across genes related to Cit and NO metabolism, which revealed genome-wide significant associations between the PRMT6 rs12028323 C allele and mood disturbance. These significant associations could be explained by the change in downstream NO signaling, supporting the relationship between the investigated traits and vascular function. These traits can be manifested as subjective symptoms of vascular aging. Therefore, the identified SNPs could predict susceptibility to the subjective symptoms of vascular aging, which could lead to genotype-based personalized interventions of Cit for an efficient improvement of vascular health.